Penerapan Sistem Monitoring Suhu dan Kelembaban Ruangan Berbasis IoT untuk Optimalisasi Pengujian Di Laboratorium Riset UPT Laboratorium Sentral Universitas Andalas - Akmecia Risqa Apriani; Taufik Try Margani; Mulda Muldarisnur (Universitas Andalas, 2026)
The quality of laboratory test results is strongly influenced by temperature and humidity conditions, therefore monitoring these parameters is essential to ensure compliance with ISO/IEC 17025:2017 standards. This study aims to develop an Internet of Things (IoT)-based temperature and humidity monitoring system accessible via the Adafruit IO platform. The system is designed using a DHT22 sensor for temperature and humidity detection, with data processing carried out by the ESP32 microcontroller, which transmits the information in realtime to Adafruit IO. The experimental results indicate that the system performs reliably in recording laboratory room conditions, with an average measurement error of 1.873% for temperature and 3.743% for humidity, while the overall accuracy reached 98,127% for temperature and 96,257% for humidity. furthermore, the ESP32 successfully transmitted data to the Adafruit IO dashboard and activated the LED and buzzer as warning indicators when the measured values exceeded the predefined thresholds.